2019
DOI: 10.1029/2019gl084666
|View full text |Cite
|
Sign up to set email alerts
|

Migrations and Clusters of Shallow Very Low Frequency Earthquakes in the Regions Surrounding Shear Stress Accumulation Peaks Along the Nankai Trough

Abstract: The spatiotemporal characteristics of shallow slow earthquake activity are linked to the tectonic environments of shallow plate boundaries. In this work, the spatiotemporal variations of shallow very low frequency earthquake (SVLFE) activity along the Nankai Trough were investigated using a cross‐correlation analysis. The SVLFEs migrated or spread eastward along the strike direction of the trench during large SVLFE episodes. Migrations and clusters of SVLFEs suggest the occurrence of shallow slow slip events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 71 publications
(122 reference statements)
7
44
0
Order By: Relevance
“…The results of previous studies (Saffer & Wallace, 2015; Takemura, Matsuzawa, et al, 2019; Takemura, Noda, et al, 2019) strongly suggested that the presence of pore fluid can control the slow earthquake activity. In Baba et al (2020), we clarified the difference in the VLFE activity inside and outside the largest coseismic slip area of the 2011 Tohoku earthquake.…”
Section: Discussionmentioning
confidence: 94%
“…The results of previous studies (Saffer & Wallace, 2015; Takemura, Matsuzawa, et al, 2019; Takemura, Noda, et al, 2019) strongly suggested that the presence of pore fluid can control the slow earthquake activity. In Baba et al (2020), we clarified the difference in the VLFE activity inside and outside the largest coseismic slip area of the 2011 Tohoku earthquake.…”
Section: Discussionmentioning
confidence: 94%
“…The source process of slow earthquakes is studied through the analysis of scaling relationships among the source characteristics: event duration, recurrence interval, size of the source fault, seismic moment release, radiated seismic energy, and so on (e.g., Ide et al., 2007; Ide & Yabe, 2014; Tan & Marsan, 2020; Yabe et al., 2019). Recent studies suggest that heterogeneities in the frictional properties on the fault control the distribution of events and their source characteristics (e.g., Baba et al., 2020; Nishikawa et al., 2019; Obara et al., 2010; Takemura et al., 2019; Tanaka et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…and shallow VLFEs(Takemura et al 2019c) as indicators of shallow slow earthquake activity. The spatial distribution of slip-deficit rates from GNSS and GNSS-A observations byNoda et al (2018), is plotted using blue contour lines in Figure11.At deeper depths (30-40 km), deep slow earthquakes were active, especially in areas with high SSE slip rates, but no interplate regular earthquakes were found.…”
mentioning
confidence: 99%